The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.775425
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Prealbumin Level and Adverse Prognosis in Patients With Hepatocellular Carcinoma After Hepatectomy: A Meta-Analysis

Abstract: BackgroundPrealbumin is a sensitive indicator of liver function and nutritional status.ObjectivesThis meta-analysis aimed to examine the association of the serum prealbumin level with the prognosis of patients with hepatocellular carcinoma (HCC) undergoing hepatectomy.MethodsWe comprehensively searched the PubMed, Embase, Wanfang, China Academic Journals (CNKI), and SinoMed databases up to September 1, 2021. Eligible studies should report the association of the serum prealbumin level with prognosis and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Some studies have confirmed the association between preoperative prealbumin levels and the prognosis of patients with HCC undergoing radical resection. Patients with low preoperative PAB levels often have a poor prognosis [ 18 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have confirmed the association between preoperative prealbumin levels and the prognosis of patients with HCC undergoing radical resection. Patients with low preoperative PAB levels often have a poor prognosis [ 18 , 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, the use of TTR is encouraged in most Asian countries such as China [72][73][74][91][92][93][94], Japan [75,[95][96][97][98][99], and South Korea [100][101][102] focusing more specific attention on matters having major public health impact. Many other Eastern countries, notably Indonesia [103], Thailand [104], India [105], Iran [106], and Australia [107] are working along similar lines, having provided substantial contributions.…”
Section: Discussionmentioning
confidence: 99%
“…It constitutes about 60% of the serum proteins by weight. Its hepatic synthesis is affected by osmotic colloid pressure and inflammatory states, but also, by nutritional status and hormones [ 5 ]. In patients with cancer, serum albumin has been found to be an independent prognostic factor for survival in various cancers such as melanoma, colorectal, pancreatic, lung, gastric, and breast cancer [ 3 , 5 7 ].…”
mentioning
confidence: 99%
“…Its hepatic synthesis is affected by osmotic colloid pressure and inflammatory states, but also, by nutritional status and hormones [ 5 ]. In patients with cancer, serum albumin has been found to be an independent prognostic factor for survival in various cancers such as melanoma, colorectal, pancreatic, lung, gastric, and breast cancer [ 3 , 5 7 ]. Furthermore, prealbumin has a shorter half-life which is about 2 to 3 days, and is considered more sensitive and accurate biomarker than albumin.…”
mentioning
confidence: 99%
See 1 more Smart Citation